2012
DOI: 10.1002/uog.11837
|View full text |Cite
|
Sign up to set email alerts
|

P06.12: PAPP‐A—a marker for gestational diabetes?

Abstract: The purpose of this study was to evaluate first trimester biochemical screening benefit with and without adding NT in enlarged measurements on screening performances. Methods: Nine thousands five hundreds and twenty-three patients underwent first trimester screening performing NT measurement and first trimester serum screening. Clinical management was decided on the basis of NT/biochemistry risk calculation. Retrospectively enlarged NT were evaluated and risk calculation was evaluated with and without NT measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study comparing the group requiring pharmacological intervention in terms of rst-trimester screening test biochemical markers and the GDM group followed only by diet, no signi cant difference was found in free hCG and PAPP-A [32]. In other studies, no signi cant relationship was demonstrated between PAPP-A in the rst trimester of pregnancy and GDM requiring insulin therapy [33,34]. In a study stating the contrary, low PAPP-A was strongly associated with GDM, and lower values were found in diabetic women who needed insulin therapy [35].…”
Section: Discussionmentioning
confidence: 95%
“…In a study comparing the group requiring pharmacological intervention in terms of rst-trimester screening test biochemical markers and the GDM group followed only by diet, no signi cant difference was found in free hCG and PAPP-A [32]. In other studies, no signi cant relationship was demonstrated between PAPP-A in the rst trimester of pregnancy and GDM requiring insulin therapy [33,34]. In a study stating the contrary, low PAPP-A was strongly associated with GDM, and lower values were found in diabetic women who needed insulin therapy [35].…”
Section: Discussionmentioning
confidence: 95%